A new species of Pristimantis (Anura: Craugastoridae) from the cloud forests of Colombian western Andes - Amézquita, Adolfo; Suárez, Gustavo; Palacios-Rodríguez, Pablo; Beltrán, Iván; Rodríguez, Camilo; Barrientos, Lucas S.; Daza, Juan M.; Mazariegos, Luis (Zootaxa, 2019)
The frogs of the genus Pristimantis are recognized for their characteristic reproductive mode and for their incredible diversity of species, becoming the genus with the highest number of species within tetrapod vertebrates. We describe here a new species of Pristimantis from the northwestern Andes of Colombia. The species was found between 2000-2500 m.a.s.l., mostly within moss hanging of tree branches in a tropical cloud forest. It can be easily distinguished from other Pristimantis species of the western Andes by the unique black and white patterning in the ventral surface and the flanks, the hourglass-shaped dorsal folds, and the prominent conical tubercles on eyelids, heels, and outer edge of tarsus. A phylogenetic analysis further supports its status of a lineage reciprocally monophyletic to P. satagius and separated by a genetic distance of 0.03; the latter species bear whitish rather than predominantly black ventral coloration. To the best of our knowledge, this species is only known from the 2,500 ha nature reserve Mesenia-Paramillo, despite other research on this area of the country. Therefore, the species is declared vulnerable while new evidence on its distribution range is accumulated.